Factors that influence celebrities' personal brands: the effects of fan club membership offers on celebrity image - Whitfield, Jill, author; Christen, Cindy T., advisor; Champ, Joseph, committee member; Diffrient, Scott, committee member (Colorado State University. Libraries, 2012)
The performing artist fan club business has recently developed into a widespread concept for generating music revenue online (Garrity, 2002). Fans have demonstrated willingness to pay to join fan club memberships offering elite benefits such as concert ticket pre-sales, meet and greet opportunities, unique merchandise, and access to exclusive news and media (Garrity, 2002). The risk with this new business model is that some fans could be insulted that they are now being asked to pay money to subscribe to their favorite artist's sites which were formerly free. This study examined the trend of celebrities charging their fans monetary fees to be members of their fan clubs, and the potential impact that this business model has on the celebrity's image. Positive or negative effects were examined by applying the theory of branding, including concepts of personal branding, internal branding and identity, external branding and image, and the Identity-based Brand Equity Model (Burmann, Hegner, & Riley, 2009). The study employed a 2x2 post-test only factorial experimental design and administered an entertainment questionnaire to 200 undergraduate college students at Colorado State University. The questionnaire examined attitudes toward one of two celebrities prior to and after exposure to an offer to join the celebrity's fan club. The fan club membership offers contained two manipulated variables: type of fan club membership (paid versus free), and celebrity and genre (pop/Lady Gaga versus country/Taylor Swift). The dependent variables in this study were the target market's attitudes toward the celebrity, and their motivation to join the fan club. Results revealed that only eight of 200 participants chose to sign up for fan club membership, regardless of the entertainer. The eight participants who chose to sign up for a fan club received a free fan club offer. Across celebrity conditions, fans are significantly more likely to find a fan club offer more appealing if it is free, and they will be more likely to join a fan club that is free rather than paid. Furthermore, liking or disliking an artist before being presented with their fan club offer greatly impacted fan motivation and likeliness to join a fan club. Fandom research and branding literature suggested that charging fees for fan club membership could negatively influence a celebrity's image. The Identity-based Brand Equity Model (Burmann et al., 2009) implied that if celebrities charged for fan club membership, and fans did not expect this or feel that the behavior aligned with the artist's brand promise, the artist's image would be negatively impacted. Study results challenged this model and indicated that fan attitudes toward both Taylor Swift and Lady Gaga did not alter when participants were presented with a paid versus free membership offer. Thus, charging for fan club membership may not support an entertainer's image, but more importantly, it will not harm an entertainer's image. These conclusions are presented to help celebrities and their management elect if they would like to charge for fan club membership. Results propose that entertainers interested in fan club monetization can apply a revenue model to increase earnings, and their image will not be harmed. Yet, artists need to think through the necessary benefits required to make paid fan clubs alluring, and take into account that fans are more likely to join fan club memberships that are free.
Keywords: celebrity; fan club; identity; image; personal brand; willingness to pay